PEMILIHAN SUPPLIER PADA RETAIL TRADISIONAL UNTUK MENINGKATKAN KEUNTUNGAN MENGGUNAKAN ANALITYCAL HIERARCHY PROCESS (AHP): Retail, Pemilihan Supplier, AHP - Kiki roidelindho; Dian Puspita Novrianti (JURNAL REKAYASA SISTEM INDUSTRI, 2018)
The supplier selection exercise is a critical factor towards the success of a bussines. This research discusses the selection of the best suppliers in traditional retail using Analytcal Hierarchy Process (AHP), where the supplier selection criteria using Quantity, Quality, Cost, Delivery model to calculate the dominant factor. The purpose of this study is To facilitate the selection of the right supplier of staples for the Traditional Retail Store. This research uses 3 suppliers as a supplier of goods for traditional retail. The results obtained from the selection of 3 suppliers obtained one supplier with the best results where the value of Quantity of 0.59, Quality of 2.01, Delevery of 1.40 and cost of 2.75 and total value obtained 6.8.